Handbook on Process Safety Integrity for Utility Operators - Janjua, Farooq (IWA Publishing, 2014)
This handbook is intended for utility operators to explain the process safety integrity issues with the focus on maintaining the long term sustainability, efficiency and effectiveness of the utility assets. It is hoped this handbook provides the basis of the essentials for managers and key engineers responsible for the ownership , operation and maintenance of assets in the utility sector.